Botulinum neurotoxin a injections influence stretching of the gastrocnemius muscle-tendon unit in an animal model - Haubruck, Patrick; Schmidmaier, Gerhard (Toxins, 2012)
Botulinum Neurotoxin A (BoNT-A) injections have been used for the treatment of muscle contractures and spasticity. This study assessed the influence of (BoNT-A) injections on passive biomechanical properties of the muscle-tendon unit. Mouse gastrocnemius muscle (GC) was injected with BoNT-A (n = 18) or normal saline (n = 18) and passive, non-destructive, in vivo load relaxation experimentation was performed to examine how the muscle-tendon unit behaves after chemical denervation with BoNT-A. Injection of BoNT-A impaired passive muscle recovery (15% vs. 35% recovery to pre-stretching baseline, p < 0.05) and decreased GC stiffness (0.531 ± 0.061 N/mm vs. 0.780 ± 0.037 N/mm, p < 0.05) compared to saline controls. The successful use of BoNT-A injections as an adjunct to physical therapy may be in part attributed to the disruption of the stretch reflex; thereby modulating in vivo passive muscle properties. However, it is also possible that BoNT-A injection may alter the structure of skeletal muscle; thus modulating the in vivo passive biomechanical properties of the muscle-tendon unit.
Gesehen am 13.09.2018